Assessing coverage of interventions for reproductive, maternal, newborn, child, and adolescent health and nutrition. (26th January 2020) - Requejo, Jennifer; Diaz, Theresa; Park, Lois; Chou, Doris; Choudhury, Allysha; Guthold, Regina; Jackson, Debra; Moller, Ann-Beth; Monet, Jean-Pierre; Moran, Allisyn C; Say, Lale; Strong, Kathleen L; et al.
Abstract : Progress has been made in priority interventions, but we need new measurement systems that include the whole life course and give better assessment of equity of coverage, argue Jennifer Requejo and colleagues